Strategic Deployment of Battery Swapping Cabinets for Phase Balancing in Low-Voltage Distribution Network - Sookananta, Bongkoj; Pusayatanont, Mongkol (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2025)
The increasing adoption of electric vehicles (EVs) has exacerbated phase imbalance in low-voltage distribution networks due to the uneven distribution of single-phase charging loads. This leads to voltage unbalance, elevated neutral currents, and increased power losses, affecting network stability and efficiency. This study explores the deployment of battery swapping cabinets (BSCs) as a non-intrusive solution to mitigate these issues. Unlike conventional phase-balancing techniques, BSCs dynamically manage charging operations without service disruptions. However, findings indicate that BSCs primarily operate in charging mode, with limited discharging due to operational constraints and service demand patterns. A stochastic optimization framework integrating Stochastic Dual Dynamic Programming (SDDP) and Monte Carlo Simulation (MCS) is developed to optimize BSC placement and energy management. Evaluating a 104-bus low-voltage network in northeastern Thailand, results show that optimized BSC deployment reduces the Voltage Unbalance Factor (VUF) by up to 30.47%, improving grid performance. The study highlights the role of BSC energy management in load balancing. These findings underscore the potential of BSCs as grid-supporting infrastructure, enhancing network resilience while reducing phase imbalance.